2000
DOI: 10.1002/(sici)1097-4636(2000)53:1<18::aid-jbm3>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

In vivo behavior of epoxy-crosslinked porcine heart valve cusps and walls

Abstract: Calcification limits the long-term durability of xenograft glutaraldehydecrosslinked heart valves. In this study, epoxy-crosslinked porcine aortic valve tissue was evaluated after subcutaneous implantation in weanling rats. Non-crosslinked valves and valves crosslinked with glutaraldehyde or carbodiimide functioned as control. Epoxy-crosslinked valves had somewhat lower shrinkage temperatures than the crosslinked controls, and within the series also some macroscopic and microscopic differences were obvious. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…21 In spite of being potential cross-linkers such as glutaraldehyde, formaldehyde, methyl glyoxal, bis-acrylamide, and epoxy-based compounds, their degradation products have been found to be cytotoxic. [22][23][24][25][26][27][28] Thus, developing a chemically benign yet a sustainable cross-linked product has become one of the top priorities for tissue engineering researchers. Generally, cations such as Ca+ 2 are the most favored ionic cross-linkers due to their tunability.…”
Section: Introductionmentioning
confidence: 99%
“…21 In spite of being potential cross-linkers such as glutaraldehyde, formaldehyde, methyl glyoxal, bis-acrylamide, and epoxy-based compounds, their degradation products have been found to be cytotoxic. [22][23][24][25][26][27][28] Thus, developing a chemically benign yet a sustainable cross-linked product has become one of the top priorities for tissue engineering researchers. Generally, cations such as Ca+ 2 are the most favored ionic cross-linkers due to their tunability.…”
Section: Introductionmentioning
confidence: 99%
“…In 1987, Nojiri et al demonstrated the possibility of calcification suppression using epoxy compounds in place of GA for cross‐linking (Nojiri, Noishiki, & Koyanagi, 1987). However, later experimental studies found that epoxy compounds cannot block the calcification of the elastin‐rich aortic wall (Rapoport et al, 2007; Van Wachem et al, 2000).…”
Section: Introductionmentioning
confidence: 99%